The port of Dublin - Hegarty, Denis A. (Statistical and Social Inquiry Society of Ireland, 1955)
My purpose this evening is to tell you something about the Port of Dublin. I shall endeavour to do this in three stages, first I shall touch briefly on its history, then I shall describe the services which are required of a large modern port, and I shall explain to you how the port is organised, controlled, operated and financed, and describe the recent improvement schemes. In the second stage, I hope with the aid of some pictures to take you on a short visit to the port so that you may see it for yourselves and, finally, in the third stage, I shall put before you some statistics relating to the shipping, trade and financing of the port.
Read before the Society, 7 January 1955
Keywords: Dublin Port; Shipping trade; 314.15